The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.1007/978-3-540-75404-6_26
|View full text |Cite
|
Sign up to set email alerts
|

The Small Outdoor Rover MERLIN and Its Assistance System for Tele-operations

Abstract: Tele-operated rovers offer huge application potential in the areas of emergency support, surveillance and security, in particular if they are small and easy to transport. In this context, the MERLIN outdoor rovers have been designed for robust operations in harsh outdoor environments at a total mass below 20 kg. The MERLIN rover system design aspects are described, including the rover on-board data processing and the sensor configuration. Special emphasis is on the remote operations assistance system, composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Up to 4 MERLIN robots (standard version) were used as stationary communication relay nodes, and one Outdoor MERLIN was used (cf. Figure 3) [21]. All MERLIN robots have a C167 microcontroller for low-level operations and sensor data processing, as well as a PC-104 for more complex and computationally more intensive tasks.…”
Section: A Used Robot Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Up to 4 MERLIN robots (standard version) were used as stationary communication relay nodes, and one Outdoor MERLIN was used (cf. Figure 3) [21]. All MERLIN robots have a C167 microcontroller for low-level operations and sensor data processing, as well as a PC-104 for more complex and computationally more intensive tasks.…”
Section: A Used Robot Architecturementioning
confidence: 99%
“…For further details on the MERLIN Control Protocol refer to [21] and [22]. As transport protocol, UDP is used which will additionally add 8 bytes for the UDP header.…”
Section: B Command and Transport Protocolmentioning
confidence: 99%
“…In Eck et al (2007), two different types of support for a tele-operator are identified, called passive and active support, respectively. Passive support is a combining term for all methods with which a system consults or advises the operator, e. g. by displaying status messages at the operator's console.…”
Section: State Of the Artmentioning
confidence: 99%
“…One is the PC of the operator, one is an Outdoor MERLIN (cf. Figure 3) (Eck et al, 2007), and two intermediate nodes are MERLIN robots (indoor version). More details on the scenario are shown in Figure 2 and a detailed description of the test setup is given in Section 2.…”
Section: Hardwarementioning
confidence: 99%